Preventive effect and mechanism of compound Danshen dripping pills on contrast-induced nephropathy after percutaneous coronary interventional - Fu, Han; Wang, Linrui; Ying, Shuo; Zhao, Zhicheng; Zhang, Peng (Frontiers in Cardiovascular Medicine, 2023)
Background: Contrast-induced nephropathy (CIN) is one of the most common complications after coronary stent implantation due to the extensive development of coronary catheterization technology. Compound Danshen dripping pills (CDDP) are clinically used as cardiovascular drugs, relieving systemic inflammatory response. Previous studies have observed that CDDP can decrease CIN incidence after coronary stent implantation with uncertain effectiveness. We conducted a prospective, randomized, single-center, single-blind, controlled trial. We enrolled patients 18 years and older with unstable angina pectoris and NSTEMI who underwent PCI at the Tianjin Chest Hospital between November 1, 2021, and November 31, 2022, and followed for 30 days. Patients were randomized to CDDP and hydration therapy (10 capsules three times/d; N=411) or hydration only (N=411). The primary outcome was the contrast nephropathy incidence, defined as an elevation in serum creatinine by more than 25% or 44 μmol/L from baseline within 48-72 hours of contrast exposure. Secondary outcomes included major adverse cardiovascular events post-surgery and during follow-up. Results: After 48 hours of operation, the two groups had statistical significance in Scr and BUN values. (80.0±12.59 vs 84.43±13.49, P<0.05; 6.22±1.01 vs 6.40±0.93, p<0.05) The difference in Scr in 72 hours between the two groups was statistically significant. (76.42 ± 10.92 vs 79.06 ± 11.58, P<0.05) The CIN incidence was significantly lower in the CDDP group than in the hydration group. The CIN risk was significantly elevated in patients with LVEF <50%, contrast volume ≥160 mL, and hypertension, after 48 and 72 hours of operation. The serum inflammation index levels NGAL, TNF-α, oxidative stress indexes SOD, and MDA significantly differed between the two groups. However, there was no significant difference in serum apoptosis indexes Bax, Bcl-2, and Casepase-9.